2013
DOI: 10.1007/s11999-012-2748-y
|View full text |Cite
|
Sign up to set email alerts
|

Smoking May Be a Harbinger of Early Failure With Ultraporous Metal Acetabular Reconstruction

Abstract: Background Smoking is considered a risk factor for surgical complications in total hip arthroplasty (THA) and has been linked to a higher rate of aseptic loosening in uncemented acetabular components. Acetabular reconstruction with newer ultraporous metals in both complex primary and revision THA has increased survivorship but it is unclear whether smoking affects survival of these implants.Questions/purposes We reviewed our early experience with THA using ultraporous acetabular components to assess the incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…However, we reported separate incidence rates for current and former smokers. The fact that the results did not substantially differ between current and former smokers in the MoM group is in accordance with the study by Lombardi et al and with the finding that the association between smoking and increased risk of nickel sensitization was present in both former and current smokers …”
Section: Limitationssupporting
confidence: 92%
See 1 more Smart Citation
“…However, we reported separate incidence rates for current and former smokers. The fact that the results did not substantially differ between current and former smokers in the MoM group is in accordance with the study by Lombardi et al and with the finding that the association between smoking and increased risk of nickel sensitization was present in both former and current smokers …”
Section: Limitationssupporting
confidence: 92%
“…The review reported an unadjusted relative risk for reoperation or revision of 1.4 (95% CI 0.6–2.1) comparing current smokers with never‐smokers and of 1.2 (95% CI 0.8; 1.6) comparing former smokers with never‐smokers, similar to our results in the CoP group. Moreover, another study evaluating one specific cup design found an increased risk of early failure among current (10%) and former smokers (10%) compared with never‐smokers (3%) . There have been no studies examining the influence of smoking on hip arthroplasty failure depending on the type of bearing surface.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Khan et al [ 11 ] defined former smokers as the patients who quit smoking over 30 days before admission to hospital, whereas former smokers in the study by Kapadia et al [ 9 ] were labeled as the patients who quit smoking over 30 days before the date of the operation. Lombardi et al [ 10 ] did not provide a definition for former smokers in their study. These characteristics may result in an under- or over-estimation of the risk.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is a modifiable patient factor that has been previously shown to increase postoperative complications [8][9][10][11][12]33,[38][39][40] . Several studies have suggested that smoking-cessation programs provide a cost-effective method of reducing complications [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%